Sosialisasi Pemetaan Arah Kebijakan Pemerintah dalam Pengembangan Badan Usaha Milik Desa di Kecamatan Dampal Selatan Kabupaten Tolitoli: Socialization Mapping the Direction of Government Policy in Development Village Owned Business Enterprises in the District Dampal Selatan Regency Tolitoli - Riadi, Slamet; Royfandi, Moh.; Farista, Gita; Vany, Suci Dwi; Wulandari, Wulandari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The purpose of this activity is to carry out outreach related to mapping the direction of Government policy in the development of Village-Owned Enterprises in South Dampal District, Tolitoli Regency. This socialization activity was carried out on July 29 2024 using the FGD (Focus Group Discussion) model and took place at the South Dampal District office involving 13 villages in the South Dampal District area. The participants who participated in this activity were the Village Head, the Head of BUMDes, the Head of the BPD, and 2 community members each representing the Village. The result of this socialization was that the participants did not know what the questions above were with an average percentage of 36.25%, while the other 21% knew what had been asked in the assessment. In the second stage of the assessment, participants showed an increase in understanding, on average they already knew what the questions above were with a presentation of 48.8% and 5.5% still answered that they did not know what had been presented in the material out of 50 active participants.